'Already existing' sustainability experiments: Lessons on water demand, cleanliness practices and climate adaptation from the UK camping music festival. Issue 103 (July 2019) - Browne, Alison L.; Jack, Tullia; Hitchings, Russell
Highlights: Sustainability experimentation research tends to focus on governance and infrastructure. Festivals are a good example of under-researched already existing collective experiments. 'Not doing' for sustainability is important, and change need not always be so effortful. The festival also highlights the importance of social legitimisation of alternative practices. Recognising flexible everyday practices as adaptive capacities is essential in climate change policy and research. Abstract: Experimentation has become a popular term amongst those interested in fostering more sustainable social futures. But the ways in which researchers and policy makers have thought about experimentation have generally been with reference to new infrastructural and governance conditions. Focusing on intentional interventions downplays the capacity for change stemming from peoples' already existing practices. In this paper, we propose that the camping music festival – a site that continues to be seen by some as a cultural laboratory in which attendees try out new identities – can be thought of as a site of 'already existing' sustainability experimentation. Drawing on 60 interviews about personal washing at two camping music festivals in the UK, we explore the festival as a site from which we can draw lessons about how societies in the Global North might cope with the disrupted water supply linked to future climate change. Interviewees divulge how escaping societal expectations about bodily cleanliness can become pleasurable and the enjoyment found in resurrecting otherwise disappearing societal skills for living without easy access to familiar washing infrastructures. Spending an extended period without these infrastructures, and enjoying the experience, brings into question the assumption of an unwavering consumer need for constant supply that is embedded in modernist visions of 'Big Water' systems. Thus, we argue that research on the geographies of 'already existing' sustainability experiments holds new potential for reimagining mundane, everyday practices within research and policy agendas on sustainable futurity.